HAK-HAK PERSONAL DALAM HUKUM PERDATA EKONOMI DI INDONESIA - Suherman, Suherman; Aryanti R, Dwi; Wahyuningsih, Yuliana Yuli (Jurnal Yuridis, 2014)
In Indonesia, the basic rights of citizens is regulated by the Constitution Law 1945 as the basis of the state constitution. Basic rights of the individual in Indonesia other than stipulated in the 1945 Constitution, as well as further stipulated in the legislation. According to the Law no. 39 of 1999 on human rights article 1, paragraph 1 determines that Human rights are a set of rights attached to nature and human existence as a creature of God is Almighty and His grace which must be respected, upheld and protected by state law , the government and everyone for the respect and protection of human dignity. The basic rights of human beings in the field of economics is the rights of economy activity, labor, right to work, earn a wage and participate in labour unions, intelectual property rights also contract field. Need further study, whether the state protects the rights of individuals in the field of civil economic law in the Indonesian . This papper By using normative methods through the study of literature. The conclusion that the government would need to make rules that are clear and detailed set of individual rights in the economic field which must refer to the basic values which are universal, namely sustainability (sustainability), unity (wholeness), harmony (harmony), equality(balance),equity(fairness)